PROMOTION OF TOUR & TRAVEL SERVICES AT PT. JAYA UTAMA WISATA IN SOLOK CITY WEST SUMATRA PROVINCE - Nabila Audrey Sylindra; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The implementation of promotions from the Travel Agent is to motivate as many pThe implementation of promotions from the Travel Bureau is to motivate as many people as possible to make purchases of sales products as well as to highlight the company's various products and attract public attention to the company's services. This research aims to find out the promotions carried out by PT Jaya Utama Wisata Tour & Travel so that they can develop and advance in achieving the target market and to find out the obstacles or obstacles in selling sales products. This study uses a qualitative method with a descriptive approach to describe and display the existing conditions at a research site by collecting data and information obtained directly from the field. The key informants in this study are the Main Director, Staff and Customers from PT. Jaya Utama Wisata Tour & Travel. In this study, the data collection techniques used were interviews, observation and documentation. From this research it can be seen that the promotion of services carried out by PT. Jaya Utama Wisata Tour & Travel is advertising, sales promotion, personal selling, direct marketing, public relations and word of mouth. Of all the promotions carried out, word of mouth is the promotion that has the most influence on product sales and purchases. But do not rule out that other promotions carried out will also affect the sales products they offer. Keywords: Travel Agent, Promotion, PT. Jaya Utama Wisata Tour & Travel